KHASIAT “SI BIJI MANIS BERTONGKOL” MENJADI SUSU SEBAGAI ALTERNATIF PENAMBAH ASAM FOLAT SELAMA KEHAMILAN - Dyan Martini; Aprilia Lusyi Wulandari; Intan Lativa Sari; Tri Yuli Astuti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract - Sweet corn - sweet corn ( Zea mays L. ) is one of the world's most important horticultural crops in addition to wheat and rice . Another a source of carbohydrates, corn is also the seasonal crops (annual) . Sweet corn provides a rich source of folic acid; health benefits for pregnant women and fetuses; can prevent underweight newborns , reducing the risk of birth defects , and it is important for fetal brain growth. One of the new breakthroughs to develop products which process them into sweet corn milk that has not been widely circulated in the community . This is because the price of corn in the market are cheap and I get it so easy. The purpose of this program is implemented (1) determine the potential of sweet corn as materials for milk containing folic acid; (2) review the analysis of the quality of sweet corn milk products; and (3) determine the potential of sweet corn milk to meet folic acid during pregnancy. Folic acid analysis methods using spectophotometric .The results obtained from this program are held to determine the content of folic acid in sweet corn, sweet corn milk determine potential to meet folic acid during pregnancy, and to determine the quality of the analysis of sweet corn products Keywords : Sweet corn , pregnant women , folic acid